Static versus dynamic evaluation in bike fitting: influence of saddle height on lower limb kinematics - Ferrer-Roca, V.; Roig, A.; Galilea, P.; Garcia-Lopez, J. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The purpose of this study was to verify if high-level cyclists achieve an appropriate kinematic pattern using their habitual bike fit. Twenty-three elite cyclists participated in the study. Many riders, 56.5%, used a habitual bike fit in which the saddle height was outside of the recommended range from 106% to 109% of the inseam. Surprisingly, however, we found an inappropriate knee flexion angle in only 26% of all the cyclists. Nevertheless, our results support the view that adjusting saddle height from 106% to 109% of the inseam would not prevent knee injuries in well-trained cyclists. Results support the contention that saddle height, inseam length and knee angle are highly related (R2=0.963 and p<0.001). We propose a novel equation that relates these factors in order to recommend an optimal saddle height.